2012
DOI: 10.4081/jphia.2012.e8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of type 2 diabetic patients regarding obesity: study in a tertiary care hospital in Bangladesh

Abstract: Prevention and management of obesity largely depends on patient motivation and education and these, in turn, can be greatly facilitated by adequate baseline data on the knowledge, attitude and practice (KAP) of patients. The aim of this study is to assess KAP on obesity among Bangladeshi type 2 diabetics. Under a cross-sectional design 160 type 2 diabetics were selected from outpatient department of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine & Metabolic Disorders. A standard que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
36
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 12 publications
(14 reference statements)
12
36
3
Order By: Relevance
“…Available online at: www.medresearch.in 483 | P a g e in India and concluded the need of starting diabetes education programs at mass level [4]. Studies from our neighboring countries like Bangladesh and Pakistan also revealed the suboptimal education and knowledge about the diabetes and emphasized on the need of effective diabetes education [5,6,7]. UP is classified as one of the 'lagging states of India' for its slow growth, low human development indicators and high concentration of the poor.…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 99%
“…Available online at: www.medresearch.in 483 | P a g e in India and concluded the need of starting diabetes education programs at mass level [4]. Studies from our neighboring countries like Bangladesh and Pakistan also revealed the suboptimal education and knowledge about the diabetes and emphasized on the need of effective diabetes education [5,6,7]. UP is classified as one of the 'lagging states of India' for its slow growth, low human development indicators and high concentration of the poor.…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 99%
“…However, studies have shown that about 35% of diabetic patients from Bangladesh do not participate in any physical activity (Saleh et al 2012). For Bangladeshi diabetic patients, this could be followed for the elevation of the complications of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Only 26.0% (27) and 32.8% (34) of the respondents read about DM and the overall health, respectively. Forty-three (41.3%), 24 (23.1%), and 6 (5.8%) of the respondents did physical activities regularly, tried to lose weight, and never took sweetened food or drinks, respectively.…”
Section: Practice Of Respondents Regarding T2dmmentioning
confidence: 99%
“…Forty-three (41.3%), 24 (23.1%), and 6 (5.8%) of the respondents did physical activities regularly, tried to lose weight, and never took sweetened food or drinks, respectively. Only 26.0% (27), and 19.2% (20) of the respondents were concerned about reducing fat and calories in their diet and had the blood test done for T2DM, respectively. Furthermore, 17.3% (18) of them always consumed sweet food and drinks, which is not a healthy practice.…”
Section: Practice Of Respondents Regarding T2dmmentioning
confidence: 99%